Desenvolvimento e avaliação de programas de treinamento para o uso do protocolo de entrevista investigativa NICHD em casos de violência sexual infantil - Blefari, Carlos Aznar (2020)
Since the 1980s, the best procedures for interviewing child and adolescent victims and / or witnesses of crimes have been discussed in international literature. Well-conducted interviews offer to the child adequate support for disclosure and allow the safety net to be activated, preventing the child’s exposure to new abusive events. In addition, they contribute to reducing the victimization and the risk of contamination. For this, investigative interview protocols were developed with the objective of helping professionals to adopt evidence-based practices in conducting their assessments. The National Institute of Child Health and Human Development (NICHD) investigative interview protocol stands out for the number of evidences of effectiveness. However, the literature demonstrates that the effects of training for the doption of the technique are not always effective and lasting in improving the quality of the interviews conducted in the field. Therefore, it is essential to evaluate instructional procedures that result in changes in the way in which interviews are conducted in the area. In this sense, in order to guarantee the right of children and adolescents to be well served by the specialized protection network, Law 13.431 / 17 that created the System of Rights of Children and Adolescent Victims and / or Witnesses of Violence. This Law has as a guideline the training of professionals on an ongoing basis and the adoption of investigative interview protocols in special testimony procedures. Based on the above, this thesis aimed to develop and evaluate training programs for the use of the NICHD investigative interview protocol and consists of three studies (one theoretical and two empirical). The first (theoretical) study: “The role of psychologists in allegations of sexual violence: Good practices in the interviews of children and adolescents” aimed to address and differentiate the role of the Psychologist in assessments of allegations of sexual violence against children and adolescents in specialized listening, special testimony and psychological expertise. The need for continued training of professionals to conduct interviews with children and adolescent victims and witnesses of violence was highlighted. The second study that composes this thesis "Evaluation of the impact of face-to-face training for the use of the NICHD investigative protocol for the evaluation of sexual violence against children and adolescents" aimed to assess the impact of a face-to-face training program for the use of the NICHD protocol. The results showed that the professionals who participated in the training were satisfied with it and noticed a positive impact on their professional practices. The longer the time spent working with victims of violence, the greater the difficulty for participants to use in practice the content learned in the training. The participants mentioned suggestions for improvement of the training, such as: conducting continuous training and conducting interviews with children and adolescents with some type of disability. Finally, the third study “Development and impact of a computer-based training for the use of the NICHD protocol in the evaluation of cases of child sexual violence” aimed to develop and evaluate the impact of a computer-based training program for the use of the NICHD protocol in the evaluation of cases of sexual violence against children and adolescents. The results indicated that the participants had high levels of reaction, impact and transfer of learning. The levels of knowledge were higher in the post-test and the reasons why some participants dropped out of the training were discussed. This thesis presents initial evidence that face-to-face training or distance learning to use the NICHD protocol has a positive impact on professionals' practices. Such results can subsidize future investments in training to comply with Law 13.431 / 17, ensuring the right of child and adolescent victims and / or witnesses to crimes to well be assisted in special deposition procedures or expert assessments.